The Unprecedented [S4N2O10]2− Anion in the Molecular Gold Complexes [Au2Br2(S4N2O10)2] and [Au2Cl2(S4N2O10)2](S2O5Cl2). Issue 65 (19th September 2022) - Rennebaum, Tobias; van Gerven, David; Wickleder, Mathias S.
Abstract: The reaction of hexachlorophosphazene, P3 N3 Cl6, with SO3 and the gold halides AuCl3 and AuBr3, respectively, leads to the new cyclic anionic tetramer, [S4 N2 O10 ] 2−, which is coordinated to Au 3+ in the dimeric complexes [Au2 X 2 (S4 N2 O10 )2 ] ( X =Cl, Br). The [S4 N2 O10 ] 2− anion can be seen as the condensation product of two sulfate anions, [SO4 ] 2−, and two amidosulfate anions, [NH2 SO3 ] − . Abstract : The cyclic anionic tetramer, [S4 N2 O10 ] 2−, is reported in dimeric gold complexes for the first time. The anion can be interpreted as the condensation product of two sulfate anions and two amidosulfate anions. The applied solvothermal synthesis between SO3, P3 N3 Cl6 and metal salts is a promising route to obtain novel nitrogen‐containing sulfates.